Laboratory studies on the effect of vibro-impact action of the screening surface on the main technological indicators of metallurgical raw material screening - Zaselskyi , V.Y.; Popolov , D.V. (Theory and Practice of Metallurgy, 2025)
The article presents the results of a study on the effect of vibro-impact action of the screening surface on the main technological indicators of metallurgical raw material screening. The screening process is one of the key technological operations in the preparatory processes of metallurgical production, as it directly influences the quality of raw material fractionation and process productivity. The issue of screen aperture clogging significantly limits the efficiency of screening, leading to a decrease in the quality of prepared charge and an increase in energy costs. The purpose of the study is to investigate the effect of vibro-impact action of the screening surface on aperture clogging and the productivity indicators of metallurgical raw material screening. To achieve this goal, a laboratory model of a vibratory screener was developed, allowing for the simulation of various vibration modes of the box and studying their impact on the raw material screening process. The research methodology included a series of experiments with varying amplitude and angular frequency of box oscillations, analysis of the results using mathematical statistics methods, and the construction of mathematical models of the dependence of transportation productivity and clogging coefficient on vibration parameters. Experiments were conducted for two types of screening surfaces – fixed and freely laid, which allowed for assessing the impact of vibro-impact loads on screen aperture self-cleaning. The results showed that maximum transportation productivity is achieved at a forced oscillation amplitude of 2·10-3 m and an acceleration of 28…32 m/s². At the same time, the clogging coefficient significantly decreases at an amplitude of 1.8…2.2·10-3 m and an oscillation frequency of 94.2…102 s-1. The constructed mathematical models allow predicting changes in the technological parameters of the process depending on the dynamic characteristics of the box and assist in selecting optimal operating modes for vibratory screeners. The scientific novelty of the work lies in determining the effect of vibro-impact action on the efficiency of metallurgical raw material screening and forming new approaches to reducing screen surface clogging. The practical significance of the study is due to the possibility of using the obtained results to modernize existing screeners and develop new designs with improved technological characteristics, which will contribute to enhancing the efficiency of preparatory processes in metallurgical production.